Molecular Identification of Resistance Genes in Staphylococcus Aureus Associated with Chronic Tonsillitis - Roaa Mohammed Hussan Al-Kinani; Huda Saad Azzawi; Zahraa Basem Alshammary (American Journal of Biology and Natural Sciences, 2026)
Staphylococcus aureus is a pathogen responsible for many cases of tonsillitis infections (bacterial tonsillitis) which occur mostly in young people and children. In our study, we tested 40 patients suffering from recurrent tonsillitis. The samples were tested microbiologically for the presence of S. aureus. Identification of the isolates was achieved through culture on Mannitol Salt Agar, Gram staining, and biochemical testing. Determination of antimicrobial susceptibility of the isolates was performed by disk diffusion testing to a range of antibiotics. DNA was extracted from selected isolates and PCR was carried out to detect the SHV gene associated with antibiotic resistance in the isolates. The PCR products were then visualized after electrophoresis in agarose gels.PCR demonstrated the presence of the SHV gene in 4 isolates of S. aureus. Rates of infection with S. aureus were greater in individuals resident in urban locations (60%) compared to those resident in rural areas (40%). There was a slight difference between male (21 cases) and female (18 cases) rates of infection. However, there was a strong association with reported use of antibiotics at time of infection (43 cases). Highest rates of isolation of S. aureus were observed in patients with chronic tonsillitis and in two age ranges; 10-20 years and 40-60 years.